Analisis Dan Perancangan Sistem Informasi Alumni (Tracer Study) Berbasis Web Pada Sekolah Tinggi Ilmu Tarbiyah (Stit) Darul ‘Ulum Sarolangun - Hidayat, Husni; Effiyaldi, Effiyaldi (Jurnal Manajemen Sistem Informasi, 2020)
At this time STIT Darul ‘Ulum Sarolangun is processing data studio that handles alumni. still done manually, by conducting conditional data collection at certain times and people, presentation of alumni data that has not been computerized (not yet using information systems). The difficulty is when facing accreditation of institutions and study programs, during the study program evaluation process, when doing stake holders need staff, the student administration has difficulty in searching for data of students who have graduated among how many alumni, gender, GPA and average score, lowest and highest, already working or not. The purpose of this research is to analyze and study the problems of alumni information systems at STIT Darul ‘Ulum Sarolangun and produce a prototype of alumni information systems at STIT Darul‘ Ulum Sarolangun. The system design in this study uses UML tools (Unified Modelling Languange) seperti use case, activity diagram, dan class diagram. Whereas in making a prototype system using MySQL tools to design a database and Adobe Dreamweaver CS6 to design a prototype system. This research produces a prototype of alumni information system that can manage alumni data, tracking study data, news data, job data, scholarship data, donation data, activity data, computerized gallery data and can present the required alumni reports. It is expected that with a computerized alumni information system, it can produce alumni information to make it easier for universities to know their alumni, as well as to produce more up to date alumni data information, the prototype of this alumni information system needs to be developed, so it can really be used online and can be applied. In developing the prototype of this information system, it has not yet paid attention to the issue of data security (security), so for that further research can be supplemented by its data security system.